2009
DOI: 10.1016/j.biomaterials.2008.12.080
|View full text |Cite
|
Sign up to set email alerts
|

Injectable in situ forming biodegradable chitosan–hyaluronic acid based hydrogels for cartilage tissue engineering

Abstract: Injectable, biodegradable scaffolds are important biomaterials for tissue engineering and drug delivery. Hydrogels derived from natural polysaccharides are ideal scaffolds as they resemble the extracellular matrices of tissues comprised of various glycosaminoglycans (GAG). Here, we report a new class of biocompatible and biodegradable composite hydrogels derived from water-soluble chitosan and oxidized hyaluronic acid upon mixing, without the addition of a chemical crosslinking agent. The gelation is attribute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
648
1
9

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 913 publications
(675 citation statements)
references
References 37 publications
17
648
1
9
Order By: Relevance
“…Motivated by this native structure, a variety of cartilage tissue engineering strategies to date have incorporated ECM, including sponges, coated scaffolds, and hydrogels of glycosaminoglycans (GAGs) or collagen, as well as decellularized tissues. [1][2][3][4][5][6][7][8][9][10][11][12][13] Whereas it is possible to generate ECM-derived scaffolds from components extracted directly from tissues, utilizing cell cultures to generate ECM/polymer composite scaffolds may be a more promising approach. This method has the added benefit of producing constructs with not only structural components, namely the polymeric scaffold and ECM components, but also the inclusion of growth factors and regulatory proteins beneficial for directing tissue regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…Motivated by this native structure, a variety of cartilage tissue engineering strategies to date have incorporated ECM, including sponges, coated scaffolds, and hydrogels of glycosaminoglycans (GAGs) or collagen, as well as decellularized tissues. [1][2][3][4][5][6][7][8][9][10][11][12][13] Whereas it is possible to generate ECM-derived scaffolds from components extracted directly from tissues, utilizing cell cultures to generate ECM/polymer composite scaffolds may be a more promising approach. This method has the added benefit of producing constructs with not only structural components, namely the polymeric scaffold and ECM components, but also the inclusion of growth factors and regulatory proteins beneficial for directing tissue regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…Weight loss study was performed in triplicates (n 5 3) and the percentage of weight loss was calculated as reported in the literature. 43 …”
Section: Hydrogel Degradationmentioning
confidence: 99%
“…Cartilage and osteochondral structures have been the main focus of attention for GAGbased scaffolds, as GAGs are particularly important components of cartilage ECM. Tan et al showed the potential of new oxidized hyaluronan/N-succinyl chitosan systems that are able to gel in situ for the delivery of chondrocytes (Tan et al, 2009). Eggelet et al tested a cell-free polyester/hyaluronan scaffold to cover microfractured full-thickness articular cartilage defects in sheep, and achieved significant improvements in histological structure, and in collagen type-II content as detected by immunohistochemistry (Erggelet et al, 2009).…”
Section: Glycosaminoglycansmentioning
confidence: 99%